2015
DOI: 10.1016/j.ijppaw.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal coccidiosis of anadromous and landlocked alewives, Alosa pseudoharengus, caused by Goussia ameliae n. sp. and G. alosii n. sp. (Apicomplexa: Eimeriidae)

Abstract: HighlightsIntestinal coccidiosis was described in anadromous and landlocked alewife populations.The same coccidian species, Goussia ameliae, was found in both population types.Sporulation dynamics and morphology of G. ameliae differed from the two populations.Goussia alosii was described in posterior intestine of landlocked populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Scarce or no differences were found between the nodular Eimeria subepithelialis and Goussia balatonica; similarly, two epicellular species (Goussia pannonica and Goussia janae) were found to be closely related. Lovy and Friend (2015) who described G. ameliae, an epicellular coccidium infecting a clupeid fish, concluded that sequences of this species show a great similarity to sequences of epicellular Goussia spp. (G. koertingi, G. pannonica and G. janae) of cyprinid fishes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scarce or no differences were found between the nodular Eimeria subepithelialis and Goussia balatonica; similarly, two epicellular species (Goussia pannonica and Goussia janae) were found to be closely related. Lovy and Friend (2015) who described G. ameliae, an epicellular coccidium infecting a clupeid fish, concluded that sequences of this species show a great similarity to sequences of epicellular Goussia spp. (G. koertingi, G. pannonica and G. janae) of cyprinid fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few representatives of fish Goussia (G. janae, G. metchnikovi, G. kuehae, G. ameliae) and three species from tadpoles (G. neglecta, G. noelleri and an unnamed Goussia sp) have yet been included in molecular phylogenies of the coccidia (Jirku et al, 2002, 2009, Gibson-Kueh et al 2011a,b, Székely et al 2013, Lovy and Friend, 2015, in spite of the fact that such Apicomplexan protozoans are prevalent in both freshwater and marine fishes (recently reviewed by Molnár, 2005, 2006and by Steinhagen et Davies, 2008. Although these sequences are dissimilar from those previously described from piscine Eimeria, sampling has not yet sufficed to determine whether other types of Goussia belong to this same lineage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…G. ameliae (Lovy & Friend, 2015) River 1.4 (14.1-21.3) 15.8 ± 0.9 (12.9-18.2) 1.1 (9.8-14.9) 6.2 ± 0.5 (4.8-7.8)…”
Section: % Mn202591mentioning
confidence: 99%
“…In the 18S rDNA-based phylogeny, some piscine coccidians (e.g. G. janae, G. ameliae, G. pannonica, G. szekelyi) form basal lineages of the species-rich eimeriorinid clade, or of its sarcocystid subclade, which encompass economically important parasites of both homeothermic and poikilothermic vertebrate hosts (Bartošová-Sojková et al 2015;Jirků et al 2002;Lovy and Friend 2015;Molnár et al 2012;Whipps et al 2012).…”
Section: Introductionmentioning
confidence: 99%